Autophagy Induction by HIV-Tat and Methamphetamine in Primary Midbrain Neuronal Cells of Tree Shrews via the mTOR Signaling and ATG5/ATG7 Pathway - Li, Juan; Wang, Wenguang; Tong, Pinfen; Leung, Chi-Kwan; Yang, Genmeng; Li, Zhen; Li, Na; Sun, Xiaomei; Han, Yuanyuan; Lu, Caixia; Kuang, Dexuan; Dai, Jiejie; et al. (Frontiers in Neuroscience, 2018)
Background: Addictive stimulant drugs, such as methamphetamine (METH), increase the risk of exposure to the human immunodeficiency virus-1 (HIV-1) infection and thus predispose individuals to the development of HIV-associated neurocognitive disorders (HANDs). Previous studies have indicated that HIV-Tat (the transactivator of transcription) and METH can synergistically induce autophagy in SH-SY5Y neuroblastoma cells and that autophagy plays a pivotal role in the neuronal dysfunction in HANDs. However, the underlying mechanism of METH-and HIV-Tat-induced neuronal autophagy remains unclear. Methods: We cultured primary midbrain neuronal cells of tree shrews and treated them with METH and HIV-Tat to study the role of METH and HIV-Tat in inducing autophagy. We evaluated the effects of the single or combined treatment of METH and HIV-Tat on the protein expressions of the autophagy-related genes, including Beclin-1 and LC3B, ATG5, and ATG7 in METH and HIV-Tat-induced autophagy. In addition, the presence of autophagosomes in the METH and/or HIV-Tat treatment was revealed using transmission electron microscopy. Results: The results indicated that METH increased the protein levels of LC3B and Beclin-1, and these effects were significantly enhanced by HIV-Tat. Moreover, the results suggested that ATG5 and ATG7 were involved in the METH and HIV-Tat-induced autophagy. In addition, it was found that mTOR inhibition could trigger autophagy and promote METH and HIV-Tat-induced autophagy. Discussion: Overall, this study contributes to the knowledge of the molecular underpinnings of METH and HIV-Tat-induced autophagy in primary midbrain neuronal cells. Our findings may facilitate the development of therapeutic strategies for METH-and HIV-Tat-induced autophagy in HANDs.